What Lessons can be Learnt from Participatory Action Research into the Emotional Wellbeing of Pupils at a Kindergarten School in Kibera Slum, Kenya? - Vohya, Sarah (2017)
Educational research has found that a child’s emotional wellbeing has a significant impact on their ability to learn, as well as predicting their future success in life. For this reason, many schools across the world have introduced social-emotional learning (SEL) programmes. However, there are very few published reports on emotional wellbeing or SEL in an African context. This study reflects on the journey and experience of conducting participatory action research (PAR) into the emotional wellbeing of pupils at a kindergarten school in Kibera slum, Kenya. The inquiry resulted in a SEL programme being introduced, which was monitored over a trial period of six weeks. The three teachers and administrator at the school were actively involved in the conception, planning, implementation and evaluation of the project. This paper highlights key lessons learnt throughout the research process, which include the challenge of upholding ideals of ‘deep’ participation, sensitivity to power dynamics, being open to the evolving nature of PAR, the importance of good communication and trust between stakeholders, and the need for context-specific research methods and interventions. It also gives recommendations for future research in this area, including steps that should be taken in order to provide a more holistic approach to fostering the emotional wellbeing of children in a context of socio-economic vulnerability.